1996
DOI: 10.1111/j.1365-2133.1996.tb06994.x
|View full text |Cite
|
Sign up to set email alerts
|

An Epstein-Barr virus-associated lymphoproliferative lesion of the skin presenting as recurrent necrotic papulovesicles of the face

Abstract: We describe four patients with lymphoproliferative lesions confined to the skin for several years. They presented with recurrent necrotic papulovesicles of the face. Latent Epstein-Barr virus (EBV) infection was detected in the lymphoid cells from the skin lesions by in situ hybridization. The disease in three patients progressed to T-cell lymphoma. We believe that these patients represent a subset of peripheral T-cell lymphoma with a tendency to localize in the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…A histopathological examination revealed perivascular and periappendageal infiltrations of atypical lymphocytes. The clinicopathological features of these patients were similar to those of previously reported cases under different names, such as edematous scarring vasculitic panniculitis, EBV associated lymphoproliferative lesion appearing as necrotic papulovesicles of the face, and angiocentric cutaneous lymphoma of childhood (14)(15)(16). Most reported patients have been children (14,16).…”
Section: Discussionsupporting
confidence: 82%
“…A histopathological examination revealed perivascular and periappendageal infiltrations of atypical lymphocytes. The clinicopathological features of these patients were similar to those of previously reported cases under different names, such as edematous scarring vasculitic panniculitis, EBV associated lymphoproliferative lesion appearing as necrotic papulovesicles of the face, and angiocentric cutaneous lymphoma of childhood (14)(15)(16). Most reported patients have been children (14,16).…”
Section: Discussionsupporting
confidence: 82%
“…This suggested that the in vitro proliferative capacity of the EBVpositive NK cells might have a correlation with the degree of malignancy. Therefore, the decrease in the requirement for IL-2 by the expanding NK-cells in the present study might explain one of the mechanisms for malignant transformation frequently reported in atypical HV (2,9,25,35,40,43).…”
Section: Discussionsupporting
confidence: 51%
“…Unlike typical HV cases, these patients were often found to have highgrade fever, liver damage, edematous swelling of the cheeks, eyelids, ears and lips, and unusual skin lesions on sun-protected areas. Noteworthy characteristics of atypical HV are an association with EBV and a tendency to develop lymphoid malignancies (2,9,25,35,40,43). Previous reports, thus, showed that both typical and atypical HV involved EBV, and atypical HV apparently had more of a tendency to lead to lymphoid malignancies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroa vacciniforme-like lymphoma (HVLL) has also been called angiocentric cutaneous T-cell lymphoma of childhood [3], and hydroa-like cutaneous T-cell lymphoma [4-6]. Most reports come from Asian area, including Japan, China and Korea [7].…”
Section: Discussionmentioning
confidence: 99%